A review of advanced practice nursing in the United States, Canada, Australia and Hong Kong Special Administrative Region (SAR), China - Judith M. Parker; Martha N. Hill (Elsevier, 2017)
This paper provides an overview of Advanced Practice Nursing (APN) in the USA, Canada, Australia and Hong Kong. It is based upon documents presented to the China Medical Board (CMB) China Nursing Network (CNN) as background for discussions held by the CNN in Shanghai. It discusses the APN role in these countries and regions according to topics identified by the CNN. These are APN educational preparation; role legitimacy; capacity requirements; scope of practice, domains of activities and limited rights for prescription and referral; professional promotion ladder; accreditation system; and, performance evaluation system. Both Canada and Australia have adapted many aspects of the USA model of APN to fit their specific legislative requirements and local conditions. Hong Kong has taken a different path which may be of interest in the Chinese context.